2021
DOI: 10.2147/jir.s293993
|View full text |Cite
|
Sign up to set email alerts
|

Altered Monocyte Subsets in Kawasaki Disease Revealed by Single-cell RNA-Sequencing

Abstract: Background: Kawasaki disease (KD) is characterized by a disorder of immune response, and its etiology remains unknown. Monocyte is an important member of the body's innate immune system; however its role in KD is still elusive due to its ambiguous heterogeneity and complex functions. We aim to comprehensively delineate monocyte heterogeneity in healthy and KD infants and to reveal the underlying mechanism for KD. Methods: Peripheral monocytes were enriched from peripheral blood samples of two healthy infants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 44 publications
2
29
1
Order By: Relevance
“…Although the etiology of KD remains unknown, several studies have shown that it might develop as a consequence of an aberrant immune response ( 114 ). This was confirmed by two different studies performing scRNA-seq in PBMCs of KD patients ( 108 , 109 ) ( Table 4 ). The first one identified 14 cell clusters in KD samples, with expanded populations of natural killer T (NKT) cells and pDC, and lower frequency of naïve CD8 + T cells, T helper cells, B cells, and lymphoid progenitor cells.…”
Section: Application Of Scrna-seq In Autoimmune Inflammatory Rheumatic Diseasessupporting
confidence: 61%
See 1 more Smart Citation
“…Although the etiology of KD remains unknown, several studies have shown that it might develop as a consequence of an aberrant immune response ( 114 ). This was confirmed by two different studies performing scRNA-seq in PBMCs of KD patients ( 108 , 109 ) ( Table 4 ). The first one identified 14 cell clusters in KD samples, with expanded populations of natural killer T (NKT) cells and pDC, and lower frequency of naïve CD8 + T cells, T helper cells, B cells, and lymphoid progenitor cells.…”
Section: Application Of Scrna-seq In Autoimmune Inflammatory Rheumatic Diseasessupporting
confidence: 61%
“…Classical monocytes in KD might thus have a less differentiated phenotype compared to their healthy counterparts. Altered monocyte subpopulations might be considered as biomarkers for KD diagnosis and treatment ( 109 ).…”
Section: Application Of Scrna-seq In Autoimmune Inflammatory Rheumatic Diseasesmentioning
confidence: 99%
“…Effects of the immune microenvironment on the pathogenesis of KD have been well-reported in many studies, and most of them underscore the importance of the innate immune system in the acute phase of KD. Particularly, levels of monocytes/macrophages and neutrophils were markedly upregulated in children with KD ( 25 , 30 , 31 ). Our results were also in agreement with these reports from high-throughput studies ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, levels of monocytes/macrophages and neutrophils were markedly upregulated in children with KD ( 25 , 30 , 31 ). Our results were also in agreement with these reports from high-throughput studies ( 30 , 31 ). In our diagnostic score, the proportion of macrophages and neutrophils weighed heavy.…”
Section: Discussionmentioning
confidence: 99%
“…Kawasaki disease (KD) is an acute, self-limiting disease that is characterized by systemic vasculitis and is the leading cause of acquired heart disease in children in developed countries [ 1 , 2 ]. KD occurs mainly in children who are younger than 5 years and is less common in older children [ 3 ].…”
Section: Introductionmentioning
confidence: 99%